PEMBERDAYAAN EKONOMI KREATIF MASYARAKAT PESISIR MELALUI KOPERASI DI KECAMATAN SUNGAI RAYA KEPULAUAN KABUPATEN BENGKAYANG - Nuraini Asriati; Sandra Fitria Wardani (STKIP Persada Khatulistiwa Sintang, 2023)
The goal of this study is to create multi-business cooperatives in the Great River Islands, Bengkayang Regency, in order to develop the potential of resource exploitation based on innovative economic empowerment and local coastal communities' wisdom. This objective is accomplished by: 1) promoting the process of empowering coastal communities' economies through cooperatives for coastal lighting; and 2) examining the application of effective creative economic models in empowering communities of fishermen in the coastal regions of the Sungai Raya islands through cooperatives. 3) Examining the barriers that prevent coastal lighting cooperatives from being more powerful. This study's initial focus is on empowering vibrant creative economy communities to respect the local coastal communities' wisdom and promote the creation of cooperative economic institutions. Via three stages-the design stage, the trial stage with a narrow focus, and the larger experimental validation stage-this research was conducted using a quantitative and qualitative approach. The study's findings show that cooperative members' economic empowerment and the creative economy owned by the neighborhood have both been very successful, and cooperative members have made an effort to diversify their product offerings by catching different kinds of fish. Fish crackers, fish floss, and other processed fish products are among the innovative goods that cooperative members attempt to manage